Absolute displacement measurement using an inertial reference generated by linearised electromagnetic levitation. (1st April 2023) - Pu, Huayan; Jing, Yan; Chen, Xu; Cao, Xijun; Yuan, Shujin; Luo, Jun; Zhao, Jinglei
Abstract: This paper proposes a novel passive absolute displacement measurement system (ADMS) utilising the electromagnetic levitation approach, instead of any mechanical spring. The most distinctive feature of the proposed ADMS is its measuring amplitude range of 30 μ m –1.2 mm with a lower frequency limit of 2 Hz. Consequently, a wider measuring bandwidth and higher measurement accuracy for absolute displacement signals can be realised without feedback/serve-type inertia sensors, which are usually expensive and vulnerable. Both features make the proposed system promising for of low-frequency measurement applications, such as precision vibration isolation of optical platforms in vibrational environments, anti-shake UAV platforms, monitoring of seismic wave signals, ship equipment protection and safety inspection of long-span bridges. First, the principles of the proposed ADMS are introduced. Subsequently, the measuring performance of the proposed ADMS is simulated and analysed. Finally, a prototype of the ADMS is constructed and tested. The experimental results confirm the validity of the proposed ADMS design and demonstrate its capability to measure the absolute displacement with a low-frequency and wider amplitude range. Highlights: An electromagnetic levitation-based method to generate quasi-zero stiffness is proposed. The inertial reference based on the quasi-zero stiffness (QZS) is utilised to sense absolute displacement. Combination of leaf springs and magnetic QZS can effectively reduce the damping and the equivalent stiffness. Lower detectable frequency (2 Hz) and wider amplitude range ( 30 μ m –1.2 mm) can be achieved.